Review of Nephelium lappaceum and Nephelium ramboutan-ake: A high potential supplement - Tsong, Jia Ling; Goh, Lucky Poh Wah; Jualang @ Azlan Abdullah Gansau; How, Siew Eng (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Nephelium lappaceum (N. lappaceum) and Nephelium ramboutan-ake (N. ramboutan-ake) are tropical fruits that gain popularity worldwide due to their tastiness. Currently, their potential to be used as pharmaceutical agents is underestimated. Chronic diseases such as cancer, diabetes and aging have high incidence rates in the modern world. Furthermore, pharmaceutical agents targeting pathogenic microorganisms have been hampered by the growing of antimicrobial resistance threats. The idea of food therapy leads to extensive nutraceuticals research on the potential of exotic fruits such as N. lappaceum and N. ramboutan-ake to act as supplements. Phytochemicals such as phenolic compounds that present in the fruit act as potent antioxidants that contribute to the protective effects against diseases induced by oxidative stress. Fruit residuals such as the peel and seeds hold greater nutraceutical potential than the edible part. This review highlights the antioxidant and biological activities (anti-neoplastic, anti-microbial, hypoglycemic actions and anti-aging), and chemical contents of different parts of N. lappaceum and N. ramboutan-ake. These fruits contain a diverse and important chemical profile that can alleviate or cure diseases.